The strategic role of social media technology in driving E-commerce firm performance: A conceptual framework - Elhachemi, Tamma; Tedjani, Mohammed Abdallah; Redouani, Hocine; Hassouna, Abderraouf (International journal of economic perspectives, 2025)
This conceptual paper explores the role of Social Media Technology Use (SMTU) in enhancing the performance of e-commerce firms, with a focus on Algeria. Drawing on the TOE framework, Resource-Based View (RBV), and Technology Acceptance Model (TAM), the study proposes a theoretical model linking SMTU to improved business outcomes such as profitability, customer engagement, and brand visibility. Based on a review of recent literature, the paper presents one key proposition and highlights contextual challenges faced by Algerian firms. The findings offer a foundation for future empirical research and practical guidance for digital strategy in emerging markets.